Results with the Boston Type I keratoprosthesis after Acanthamoeba keratitis - Santos, Albert (Am J Ophthalmol Case Rep, 2017)
PURPOSE: To report the outcomes of implantation of the Boston Type I keratoprosthesis in three patients with Acanthamoeba keratitis (AK), a severe infection that can lead to significant visual loss. OBSERVATIONS: Case series reporting three patients with difficult cases of AK that needed multiple corneal transplantations and glaucoma surgeries. All patients were implanted with the Boston Type I keratoprosthesis device. The main outcomes measure were the visual function and anatomical retention after implantation of the Boston Type I keratoprosthesis. All patients retained the device over the long-term and had good visual function. In one patient a retroprosthetic membrane developed and in another patient an epithelial lip developed over the anterior surface of the keratoprosthesis. The visual acuities range from 20/25 to 20/80 in the implanted eyes. CONCLUSIONS AND IMPORTANCE: The Boston Type I keratoprosthesis resulted in good anatomic and functional results after multiple graft failures after AK.